MATEMÁTICA MODERNA NO CURSO PARA PROFESSORES DA ESCOLA NORMAL EM NATAL/RN (1971) E NO COLÉGIO ATHENEU NORTE-RIO-GRANDENSE (1970): ALGUMAS REFLEXÕES (RevistAleph, 2014)
Resumo: Neste artigo, apresentamos e descrevemos vestígiosencontrados acerca do ensino de Matemática no RN, durante a décadade 1970, relacionados à Matemática Moderna. Estes vestígios foramevidenciados no curso para professores da Escola Normal que houveem Natal/RN (1971), bem como nas aulas de Matemática no ColégioAtheneu (1970). Para elaborar esta história, respaldamo-nos empressupostos teóricos da História Cultural. Analisamos as fontesescritas e orais que utilizamos, classificamos os documentos eempregamos a intertextualidade, buscando regularidades edistanciamentos entre as fontes.PALAVRAS-CHAVE: Ensino. Matemática Moderna. Escola Normal.Abstract: In this article, we present and describe traces found on theteaching of Mathematics in RN, during the 70’s, related to ModernMathematics. These traces were detected in the course for Teachers inNormal Schools who were in Natal/ RN (1971), as well as inmathematics classes at the College Atheneu (1970). To elaborate thisstory, we used as theoretical foundation assumptions of CulturalHistory. We analyzed the written and oral sources we used, classifieddocuments and used intertextuality, seeking regularities anddifferences between the sources.KEY-WORDS: Teaching. Modern Mathematics. Normal School.